Pengembangan Aplikasi E-Canteen Dengan Pembayaran Non-Tunai Berbasis Android Untuk Siswa (Studi Kasus: SMA Negeri 5 Malang) - Vega Revaldy; Widhy Hayuhardhika Nugraha Putra; Buce Trias Hanggara (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2020)
E-canteen system is a canteen management based on android system to make ordering food and beverage easier. This whole time, ordering food system based on the application has not been existed. The ordering food system at SMAN 5 Malang is applied manually. The students have to queues to order the menu they are desired. The food vendors also have some difficulty when they don't have small change. And because they can only take orders during the break time, it also impacted their income due the very limited time available. The problems above have inspired the developing of the e-canteen apps. The app makes the transaction easier. The payment now is become cashless. The students are equipped with QR-code features to top up their balance. The cashless payment is used to deduct the balance on the students' apps. When they have sufficient balance on their account for the total payment, it will be deducted automatically from their account by system. While for the insufficient balance, the transaction will be canceled automatically. E-canteen is developed using waterfall model because it was made step by step. The functional requirements testing was done using the black-box method. The test result was proved to be 100% valid from 22 functions that have been tested.